Characterization and targeting of metabolic alterations in the leukemic microenvironment - Vélez Luján, Juliana (2016)
The bone marrow microenvironment is an important determinant for normal and malignant hematopoiesis. Bone marrow mesenchymal stromal cells (BM-MSCs), endothelial cells, osteoclasts and osteoblasts promote the maintenance and survival of quiescent leukemia initiating cells via cell contact and paracrine signaling pathways. However, other components of this microenvironment such as platelets have not been studied and their precise role remains incompletely understood. In contrast, one of the most studied interactions have been between BM-MSCs and leukemia cells, which promote mitochondrial uncoupling -a disconnection between the electrochemical gradient of the mitochondrial membrane and the oxidative phosphorylation (the major source of cellular ATP)-, Characterized by an increase of resistance to intrinsic apoptosis, decrease of entrance of pyruvate into the Krebs cycle presumably to use glucose carbon skeletons for the generation of biomass, and a shift to the metabolism of fatty acids to support oxygen consumption. Previous evidence demonstrated that pharmacological inhibition of fatty acid oxidation (FAO) sensitizes leukemia cells to Intrinsic apoptosis, suggesting that targeting carbon utilization in the context of mitochondrial uncoupling may be a valid therapeutic strategy. However, inhibition of fatty acid oxidation may not be a feasible clinical strategy due to chronic toxicity. Whether other metabolic parameters can be targeted with clinically available drugs for the therapy of leukemia remains to be determined. Based on these antecedents, we decided to investigate if platelets play a role In promoting leukemia cell survival. Our work indeed demonstrates that platelets promote survival of leukemia cells, in part by promoting mitochondrial uncoupling and increased reliance on FAO in much the same way as BM-MSC. Given that FAO relies on increased electron transport we also investigated if the antidiabetic drug Metformin, which has been shown to partially inhibit the electron transport chain (ETC), could overcome the metabolic reprogramming of leukemia cells and sensitize them to the induction of apoptosis. Lastly, given that increased FAO results in depletion of intracellular oxygen and very likely promotion of glycolysis and accumulation of lactate as a consequence, we questioned if hypoxia activated pro-drugs (PR-104, TH-302) and pH sensitive peptides (pHLIP) would be effective therapeutic agents for the treatment of leukemia. Our results evidenced the resistance to targeted therapy induced by platelets through mitochondrial uncoupling, which could be potentially overcome by the use of Metformin and other agents (PR-104,TH-302, pHLIP) affecting several of the metabolic re-arrangements found in leukemia cells. The results generated from these experiments will advance our understanding of leukemia cell survival and metabolism In its microenvironment, and potentially provide scientific rationale for the use of Metformin, Hypoxia activated pro-drugs and pH sensitive peptides for the treatment of the leukemic bone marrow.